ANALISIS MAKNA PADA LIRIK LAGU ALENIA KARYA BATAS SENJA DENGAN PENDEKATAN SEMIOTIKA - Meriska Yosiana; Chintia Handayani (Asosiasi Dosen Muda Indonesia, 2024)
This research focuses on analyzing the meaning of the lyrics of the song Alenia by Batas Senja. The lyrics of the song Alenia are the first hit single released by the indie band Batas Senja in 2007. The meaning of the song lyrics is important because it is an expression from the songwriter to the public. The aim of this research is to find out the meaning contained in the lyrics of the song Alenia using Ferdinand de Saussure's semiotic approach. Saussure's semiotics focuses on signifier and signified. The method used to analyze data was a qualitative descriptive method. This method was used because the data are in the form of words. The result of this research showed that the meaning contained in the lyrics of the song Alenia is the story of the life journey of someone who fought persistently and never gave up in facing all the trials of life. Besides that, to keep moving forward and not be afraid to always try new things so that it does not just produce a monotonous story. This song encourages listeners to pursue their dreams and aspirations with full determination. This message reminds us not only to dream, but also to act and try to make it happen. Therefore, this song inspires us to keep running to look for new things in life and not stop until our goals are achieved.